Acquisition of Land Property by Foreigners in Poland in 2000-2010 - Lizińska, Wiesława; Marks-Bielska, Renata (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
The objective of the present study has been to evaluate changes in the number of sales and in the area of land real estate, including agricultural and forest land, bought by foreigners in 2000-2010, and also in the land real estate acquired via transactions such as acquisition or taking hold of stocks and shares in companies which had been owners or perpetual users of real estate. The authors have used secondary data from the Ministry of Interior and Administration3, the Institute of Agricultural Economics and Food Economy, the Agricultural Property Agency (APA) and the Ministry for Agriculture and Rural Development. Most agricultural and forest land and other types of real estate sale transactions were concluded in 2007. In 2000-2010, foreigners bought land real property with total acreage of 37,588.57 hectare. Since 2008, a dynamic increase has been observable in the area of land property purchased through transactions of acquisition or taking hold of stocks and shares by foreigners in companies which had been owners or perpetual users of real estate (in 2006-2010, foreigners bought 75.4% of the total area of land bought in this way). In 2000-2010 foreigners acquired in total 65,731.79 hectare of land real estate in Poland, while the total area of land sold from the resources of APA during the same time period was 1,228,000 hectare.